Project-Based Blended Learning Model to Enhance Collaborative Skills of University Students: Model Pembelajaran Blended Learning Berbasis Proyek untuk Meningkatkan Keterampilan Kolaborasi Mahasiswa Perguruan Tinggi - Indah Farida (Journal of Educational Research and Learning Analytics, 2025)
Blended Project-Based Learning (BPjBL) integrates face-to-face and online modalities to foster collaboration skills essential for 21st-century higher education. This study employed a quasi‐experimental pretest–posttest control group design involving 120 economics undergraduates from semesters 3 to 5. Sixty students experienced BPjBL, while sixty served as controls under conventional instruction. A rubric measuring active contribution, productivity, flexibility, responsibility, and mutual respect assessed collaboration, validated through expert judgment and yielding a Cronbach’s alpha of 0.87. Over eight weeks, the BPjBL group engaged in project design, digital execution, monitoring, public presentation, and reflective evaluation across blended phases. Independent‐samples t‐tests revealed significant improvements in collaboration scores for the BPjBL group compared to controls (p < 0.05). Descriptive analyses illustrated enhanced dynamics in each learning phase. These findings indicate that BPjBL effectively combines flexibility and authentic project contexts to develop collaborative competencies. Implementing BPjBL in higher education can support deeper student engagement and prepare learners for complex real‐world teamwork challenge.